CASE TECHNOLOGY IN THE SYSTEM OF DISTANCE EDUCATION - Pardaev, Mamasharif (Журнал иностранных языков и лингвистики, 2021)
This article is about using case technologies in distance education. It analyzes the technology of problem learning as an innovative direction in the modern educational process.